2015
DOI: 10.15585/mmwr.mm6446a4
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs: Estimated Percentages and Numbers of Adults with Indications for Preexposure Prophylaxis to Prevent HIV Acquisition — United States, 2015

Abstract: Clinical organizations, health departments, and community-based organizations should raise awareness of PrEP among persons with substantial risk for acquiring HIV infection and their health care providers. These data can be used to inform scale-up and evaluation of PrEP coverage. Increasing delivery of PrEP and other highly effective HIV prevention services could lower the number of new HIV infections occurring in the United States each year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
240
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(250 citation statements)
references
References 10 publications
3
240
2
5
Order By: Relevance
“…The CDC estimates that about 1.2 million persons in the U.S. are eligible for PrEP. 9 Although we do not know the exact proportion of PCPs who provide care to persons eligible for PrEP, the fact that the vast majority of persons who are eligible are not receiving PrEP underscores the need to increase the number of PCPs offering PrEP to eligible individuals. 10 Second, as PCPs providing care to greater than 50 HIV-positive patients were more likely to report PrEP adoption than those providing no HIV care, provider-focused educational initiatives to enhance PrEP adoption may need to target those without HIV care experience, as well as training those with HIV care experience to be PrEP "clinical champions".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDC estimates that about 1.2 million persons in the U.S. are eligible for PrEP. 9 Although we do not know the exact proportion of PCPs who provide care to persons eligible for PrEP, the fact that the vast majority of persons who are eligible are not receiving PrEP underscores the need to increase the number of PCPs offering PrEP to eligible individuals. 10 Second, as PCPs providing care to greater than 50 HIV-positive patients were more likely to report PrEP adoption than those providing no HIV care, provider-focused educational initiatives to enhance PrEP adoption may need to target those without HIV care experience, as well as training those with HIV care experience to be PrEP "clinical champions".…”
Section: Discussionmentioning
confidence: 99%
“…2 The CDC estimates that 1.2 million individuals are eligible for PrEP based on sexual and drug use behaviors, yet only about 80,000 unique individuals have been prescribed PrEP since its 2012 approval by the Food and Drug Administration. 9,10 Moreover, studies suggest that only a minority of U.S. health care providers report having ever prescribed PrEP. [11][12][13][14][15][16][17] Health care providers play a central role in the implementation of new health-related technologies, given their access to individuals or populations that might benefit most.…”
Section: Introductionmentioning
confidence: 99%
“…By 2015, Truvada® had the largest market share (17%) of all HIV drugs with no competing HIV drugs on the market for prophylaxis. The potential market for PrEP is estimated as 1.2 million people, including 25% of the estimated 4.5 million men who have sex with men (MSM) in the US [10][11][12]. The 2 of 18 average wholesale price of Truvada® was $1,646 for a 30-day supply in 2015 whether used for prevention or treatment of HIV [13].…”
Section: Introductionmentioning
confidence: 99%
“…Compare those initial prevention responses to subsequent approaches, informed by theory and evidence, that tested interventions based on theoretically derived models of behavior change, delivered by engaging the social networks of vulnerable populations [5]. Or reckon how randomized controlled trials have demonstrated the efficacy of pre-exposure prophylaxis (PrEP) in preventing HIV infection among men who have sex with men [6] as well as heterosexual men and women [7]; if brought to scale and provided in tandem with other effective HIV prevention methods, there is little doubt that PrEP could substantially reduce the number of new HIV infections among at-risk populations [8].…”
mentioning
confidence: 99%